Influence of Moringa oleifera on General and Hemato-biochemical Parameters in Arsenic Induced Japanese Quails (Coturnix coturnix japonica) - Ther, Sandip Vishnu; Kale, Meena Madhukar; Mahajan, Namrata; Pathak, P. Vinaya; Joshi, Madan V. (Indian Journal of Animal Nutrition, 2018)
The present study was conducted to investigate the effect of inclusion of Moringa oleifera seed powder in the diet on intake, growth performance and hemato-biochemical parameters in arsenic induced Japanese quails Group T1 was fed with commercial feed which served as control and group T2 was fed 300 ppm of arsenic trioxide with commercial feed. Group T3 and T4 were fed with 5 and 10% of M. oleifera seed powder, respectively while group T5 and T6 were fed 5 and 10% of M. oleifera with 300 ppm arsenic trioxide, respectively. Higher body weight gain was found in group T3 as compared to other groups. Arsenic fed birds exhibited lower level of Hb while M. oleifera fed birds had higher level of Hb. In group T2, egg production was reduced incomparison to other groups. Hence, feeding of M. oleifera seeds powder @ 5 and 10% improved the ill effects of feeding 300 ppm arsenic in Japanese quails.